ПРОБЛЕМА ИДЕНТИЧНОСТИ В УСЛОВИЯХ КУЛЬТУРНО- ЦИВИЛИЗАЦИОННОЙ ДУАЛЬНОСТИ - Старикова, Г. Г. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Статья посвящена проблеме специфики культурно-цивилизационной идентичности в ситуации глобализационных вызовов. Анализируется роль дихотомии «традиционное- современное» в социокультурных трансформациях современного общества. Г.Г. Старікова ПРОБЛЕМА ІДЕНТИЧНОСТІ В УМОВАХ КУЛЬТУРНО-ЦІВІЛІЗАЦІЙНОЇ ДУАЛЬНОСТІ Статтю присвячено проблемі специфіки культурно-цивілізаційної ідентичності у ситуації глобалізацій них викликів. Аналізується роль дихотомії «традиційне-сучасне» у соціокультурних трансформаціях сучасного суспільства. Ключові слова: ідентичність, культурно-цивілізаційна специфіка, глобалізаційний виклик, абсентеїстська раціональність. G. Starikova THE PROBLEM OF IDENTIFICATION IN THE TERMS OF CULTURE-CIVILIZATION DICHOTOMY The article is devoted the problem of specific the culture-civilization identification in the situation of global challenge. The role of dichotomy “traditional-modern” in the social-cultural transformation is analyzed. Key words: identification, culture-civilization specific, global challenge, abstention rationalism.